(untitled) (Advancements in Homeopathic Research, 2024)
Liver diseases pose a serious health challenge in India, impacting roughly 20% of the population and standing as a leading cause of mortality. Traditional treatments often fall short, especially in rural areas with limited healthcare access. Homeopathy in general has shown its effectiveness. This study investigates the hepatoprotective activity of Alpha™-Liv Drops, a homeopathic formulation, to explore its potential treatment option for liver diseases in the Indian healthcare landscape.